Design and implementation of navigation control system based on CPCI - Yan Jiachen; Zhang Haonan; Zhang Shaopeng; Cui Tao; Li Hao; Guo Yu (Dianzi Jishu Yingyong)
Aiming at the requirements of high-precision trigger control, timing control, and real-time performance in marine seismic exploration integrated navigation systems, a navigation operation control system based on the CPCI bus architecture has been designed. This system incorporates a built-in GNSS receiver and achieves high-precision clock maintenance through GPS time, FPGA and embedded software. The system utilizes a star topology differential line for high-speed serial transmission interface communication, supporting up to 24 serial port data connections. The high-precision trigger module and time-stamp matching rules enable real-time and precise control of external equipment. This paper focuses on the interface, module structure, embedded software, and experimental results. System test shows that the platform fulfills the requirements for high-precision timing and operation process sequence control in marine seismic exploration. The system is modularly designed, offering excellent scalability and modular encapsulation, and serves as a valuable reference for the development of other industrial control system.